Powder-mixed electro-discharge diamond surface grinding process - Modi, Manoj (Strojniški vestnik, 2013)
Powder-mixed electro-discharge diamond surface grinding (PMEDDSG) is an efficient process for shaping hard materials, such as Ti-6Al- 4V. Modelling, comparative analysis to study the behaviour of input variables against the responses for both processes, determination of optimum combination of parameters, and studying the effect of input variables on white recast layer thickness and finally on different surface generation during the PMEDDSG processing of Ti-6Al-4V are reported in this paper. The response surface methodology was used to develop the mathematical models of both the responses. Thirty-one experiments were performed on the PMEDDSG set-up without powder-mixed dielectric fluid. Another thirty-two experiments were performed on the PMEDDSG set-up with aluminium powder-mixed dielectric fluid. The current, pulse-duration, wheel-speed, duty-cycle and powder-concentration (considered only as an input variable with the powder-mixed dielectric fluid) were taken as input parameters. The material-removal-rate (MRR) and average-surface-roughness (Ra) were measured as responses in both the process. The weighted principal components (WPC) analysis has been applied to find an optimum setting of PMEDDSG process parameters during multi-output optimisation. A total of 18 experiments were performed according to Taguchi L18 orthogonal-array on the PMEDDSG set-up. The optimum combination suggested by the WPC method was tested to obtain the optimum values of MRR and Ra. The scanning electron microscopy images showed that the surface view and white recast layer thickness of machined workpieces are largely influenced by ampere-current, pulse-duration, duty-cycle, wheel-speed and powder-concentration.
Keywords: analiza variance; diamantno površinsko brušenje; diamond surface grinding; EDDSG; elektroerozijska obdelava; PMEDDSG; powder-mixed electro-discharge; Ti-6Al-4V; utežene glavne komponente; weighted principal components; WPC